Compartment Syndrome of the Foot: An Evidence-Based Review - Lutter, Christoph; Schöffl, Volker Rainer; Hotfiel, Thilo; Simon, Michael; Maffulli, Nicola (Journal of Foot & Ankle Surgery, 2019)
Compartment syndrome of the foot (CSF) is a surgical emergency, with high risk of morbidity and poor outcome, including persistent neurologic deficits or amputation. Uncertainty remains regarding surgical approaches, pressure monitoring values, and the extent of surgical treatment. This review provides a summary of the current knowledge and reports evidence-based diagnostic and therapeutic management options for CSF. Articles describing CSF were identified from MEDLINE, PubMed, and Cochrane databases up until February 2018. Experimental and original articles, systematic and nonsystematic reviews, case reports, and book chapters, independent of their level of evidence, were included. Crush injuries are the leading cause of CSF, but CSF can present after fractures of the tarsal or metatarsal bones and dislocations of the Lisfranc or Chopart joints. CSF is often associated with persistent neurologic deficits, claw toes, amputations, and skin healing problems. Diagnosis is made after accurate clinical evaluation combined with intracompartmental pressure monitoring. A threshold value of <20 mmHg difference between the diastolic blood pressure and the intracompartmental pressure is considered diagnostic. Management consists of surgery, whereby 2 dorsal incisions are combined with a medioplantar incision to the calcaneal compartment. The calcaneal compartment can serve as an “indicator compartment,” as the highest-pressure values can regularly be measured within this compartment. Appropriately powered studies of CSF are necessary to further evaluate and compare diagnostic and therapeutic options.
CRIS-Team Scopus Importer:2019-07-09
Keywords: 3; fasciotomy; foot injury fracture; intracompartmental pressure; pressure monitoring; trauma